Mitos Sange Serri dalam Proses Mapatappe pada Suku Bugis di Kelurahan Noling Kecamatan Bupon Kabupaten Luwu - Misra Nengsi (Rayhan Intermedia, 2018)
This study aims to find out: (1) The history of the emergence of the sange serri myth in the mapatappe process of the Bugis Tribe in Noling Village, Bupon Subdistrict, Luwu Regency, (2) The Bugis Tribe belief system in Noling Village in the myth of sange serri in the mapatappe process, (3) Implications trust in the myth of Sange Serri in the process of mapatappe. The technique of data collection is done through documentation, observation, and interviews and the data is processed using descriptive qualitative methods. The results of the study show: (1) The emergence of the myth of Sange Serri in the mapatappe process stems from the knowledge of the community about the meaning of the house which is divided into three parts and especially those relating to the roof or zinc. In line with that there is also the belief of the ancestors about crop failures that occur when not completing the mapatappe process in a day. The mapatappe myth is still believed by the local community as a heritage of their ancestors. (2) Reasons for the Bugis Tribe to still believe in the myth of Sange Serri in the mapatappe process, because there is a personal experience of the community about the consequences of the myth of mapatappe such as crop failure if it cannot complete the mapatappe in a day. (3) The implication of this belief has a positive impact, namely the Noling community is still very thick with the culture of mutual cooperation, while the negative impact is the existence of material losses and lack of knowledge of people who believe in the myth of mapatappe.